Faktor Penghambat Pelaksanaan Rehabilitas Anak Pengguna Narkoba Di Lembaga Pembinaan Khusus Anak (International Forum of Researchers and Lecturers, 2024)
This research discusses the Implementation and Inhibiting Factors of Rehabilitation of Children as Drug Users at the Gorontalo Children's Special Development Institution. The method used in the research is empirical with qualitative descriptive data analysis which describes and describes data and facts in the field. Based on the results of the research, the implementation of rehabilitation for children as drug users at the Gorontalo Province Special Child Development Institute is carried out through several stages, namely medical rehabilitation which begins with assessments and interviews as well as observations to examine the body and psychology in order to obtain information and history of narcotics addicts as supporting material for subsequent therapy. After the assessment, the next step is a routine examination process every 2 weeks by a health team or doctor, and administering medication according to the type of drug and the severity of the symptoms caused; Non-medical rehabilitation by carrying out a mental (spiritual) development process which is carried out routinely every day, in collaboration with religious foundations; and Social Rehabilitation by creating groups consisting of several people who have the same problem, then training in their skills to make work or crafts that have (economic) value. The Inhibiting Factors for Implementing Rehabilitation for Children who Use Drugs at the Gorontalo Province Special Development Institution for Children are limited human resources for officers; Limited Operational Funds; limited facilities and infrastructure, and lack of community support.Therefore, LKPA should continue to increase efforts to develop children so that they do not do similar things again in the future, by preparing rehabilitation infrastructure, including increasing competent and professional assistant staff. The community, especially families, must continue to provide full support for the process of coaching their children who are dealing with legal processes such as drugs, for the sake of the future of the nation and state.